The transcriptome expression levels related to ovulation induction and acupuncture protection therapy in rats through gene microarray. Issue 1 (31st December 2022) - Li, Qian; Gong, Meirong; Shen, Jie; Jin, Xun; Mu, Yanyun; Xia, Liangjun; Cheng, Jie; Xia, Youbing
ABSTRACT: This study aimed to explore the potential molecular mechanisms of acupuncture in the adjuvant treatment of infertility. A rat model of ovulation induction was constructed using horse serum gonadotropin and human chorionic gonadotropin, and then acupuncture was used to treat the model rats at Guanyuan and Sanyinjiao points. Hematoxylin eosin (HE) staining, the endometrial thickness, and enlargement of uterine cavity were determined to evaluate the effects of acupuncture on the uterus of ovulation induction rats. Meanwhile, the uterus tissues were sent for gene microarray analyses. Acupuncture enhanced the endometrial receptivity of ovulation induction rats. Gene microarray showed that 189 overlapped differential expressed genes (DEGs) were identified, and these overlapped DEGs were divided into four clusters by Mfuzz algorithm. Afterwards, interaction networks containing 842 interaction pairs were established, and the DEGs in the interaction networks were significantly enriched in 20 BP and 10 KEGG pathways, including wound healing, response to glucocorticoid, TNF signaling pathway, terpenoid backbone biosynthesis, and glutathione metabolism. By calculating topological parameters, Anxa5, Casp8, Tgm2, Frk, Mmp7, Timp1, Hmgcr, Cth, Serpinal, and Abcbla were the important hub genes of the interaction networks. Our findings revealed the changes at transcriptome levels related to ovulation induction and acupuncture protection therapy.